2006
DOI: 10.1097/01.sla.0000237743.22633.01
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nonoperative Management of Penetrating Abdominal Solid Organ Injuries

Abstract: In the appropriate environment, selective nonoperative management of penetrating abdominal solid organ injuries has a high success rate and a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
220
4
35

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(266 citation statements)
references
References 33 publications
7
220
4
35
Order By: Relevance
“…NOM failure increased length of hospital stay and increased mortality in selected subsets of patients (9,32). Accordingly, NOM has shorter length of hospital stay than operative management in patients with isolated solid organ injuries (30). In contrast, the length of hospital stay of NOM group was shorter in this study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…NOM failure increased length of hospital stay and increased mortality in selected subsets of patients (9,32). Accordingly, NOM has shorter length of hospital stay than operative management in patients with isolated solid organ injuries (30). In contrast, the length of hospital stay of NOM group was shorter in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…In addition to blunt trauma, NOM also can be applied for penetrating traumas. Dematriades et al (30) applied it liver in 28.4% of selected patients, kidney in 14.9%, and spleen in 3.5%. In our study, seventy-one patients who suffered from blunt and, six from low-grade penetrating injuries were treated non-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed on 152 patients with penetrating liver trauma revealed that 125 patients (82.2 %) were operated upon due to hemodynamically instability and 27 patients (17.8 %) were treated with NOM due to hemodynamic stability. All these patients were evaluated with serial physical examination and CT scan [15]. These studies support the fact that NOM of the selected cases of penetrating liver trauma is safe especially if the patient was hemodynamically stable.…”
Section: Discussionmentioning
confidence: 58%
“…NOM is intended in around 65 % of the blunt liver injury cases with success rates of about 90 % [2•, 17]. For penetrating trauma, NOM is intended in about 30 % of cases with success rates of around 80 % [18,19]. Endovascular interventions are indicated to aid NOM when clinical or imaging findings suggest persistent liver hemorrhage [7].…”
Section: Hepatic Injurymentioning
confidence: 99%